The development of ocean currents and the response of the cryosphere on the Southwest Svalbard shelf over the Holocene - Devendra, Dhanushka; Łącka, Magdalena; Szymańska, Natalia; Szymczak- Zyła, Małgorzata; Krajewska, Magdalena; Weiner, Agnes K M; De Schepper, Stijn; Simon, Margit H; Zajączkowski, Marek (PANGAEA, 2025)
We present multi-proxy data, including benthic foraminiferal assemblages, carbon and oxygen stable isotopes, total organic carbon (TOC) and total carbon (TC), ice-rafted debris (IRD), x-ray fluorescence, biomarkers (alkenones, sterols), and pigment data, covering the past 11.4 kyr BP. These data are derived from sediment core OCE2019-HR7-GC, retrieved from the Southwest Svalbard shelf (76°56.513'N, 14°54.072'E, 133 m water depth) during the AREX 2019 expedition aboard RV Oceania. Benthic stable isotopes were primarily measured on Elphidium clavatum. The dataset is presented in relation to both age and depth.
Keywords: Biomarkers; Foraminifera abundance; Foraminifera flux; Foraminiferal stable isotopes; Holocene; Ice Rafted Debris; Organic carbon; Pigments; Southwestern Svalbard shelf